Improving the Students' English Skills through Online Activities in Moodle Platform - Didik Hariyadi Raharjo; Ilza Mayuni; Emzir Emzir (Langkawi: Journal of The Association for Arabic and English, 2020)
This research was aimed to determine the effectiveness of online instructional material model for EFS courses developed through Moodle for Secretarial Academy (ASTRI) of Budi Luhur students when compared to the existing EFS instructional material. This qualitative research conducted in the second semester of 2007/2008 academic year. Meanwhile the data sources used in this study were respondents consisting of 48 ASTRI Budi Luhur students as well as documents consisting of observation guidelines and post test results. The students were divided into 2 classes, namely BA and BB classes. BA class is treated as an experimental class while BB class is treated as a control class. This experiment was carried out for 7 times fully online learning with synchronous learning method. In analyzing the data collected, the researchers used T-Test to find out the effectiveness of EFS instructional material through Moodle. Based on the results of the post test conducted, EFS instructional material through Moodle had been proven to be able to improve four english skills which include listening, reading, speaking and writing to the students of ASTRI Budi Luhur Jakarta.